Effects of Major Selection Motivation and Major Satisfaction of College Students Majoring in Artificial Intelligence on Their Adaptation to College Life - Zhao, Mengna; Lee, Seungjin (Journal of Educational Research and Policies, 2025)
This study focuses on university students majoring in artificial intelligence at S University in Zhejiang Province, aiming to reveal the relationships among major selection motivation, major satisfaction, and adaptation to college life, as well as the mediating role of major selection motivation on major satisfaction. The objective is to examine whether it influences adaptation to college life. Based on previous research and theories, research hypotheses were established, and a survey was conducted among 340 university students from the first to the fourth year majoring in artificial intelligence at S University in Zhejiang. The data were analyzed using SPSS 26.0 and AMOS 26.0. To understand the impact of major selection motivation and major satisfaction on adaptation to college life, a structural model analysis was performed, with the following results. In the relationship between major selection motivation and major satisfaction, it was confirmed that major selection motivation has a significant direct effect on major satisfaction, and major satisfaction plays a significant mediating role in the relationship between major satisfaction and adaptation to college life. Therefore, to enhance the adaptability of university freshmen to college life, it is necessary to provide career guidance based on their interests or abilities during the process of selecting a major upon entering university. Furthermore, there is a need for institutional arrangements to offer various educational services and programs related to major satisfaction.